Computed tomographic evaluation of the proximity of needles placed for perineural anesthesia of the palmar digital nerves to synovial structures in the foot: an ex vivo study - Gruyaert, Mounia; Oosterlinck, Maarten; Haspeslagh, Maarten; Nagy, Annamaria (Frontiers in Veterinary Science, 2024)
Background Potential synovial penetration following palmar digital nerve blocks has not been investigated. Objectives To evaluate the proximity of needles placed for palmar digital nerve blocks to nearby synovial structures using computed tomography (CT). Study design Descriptive observational study. Methods In 18 cadaver forelimbs, sequential injection of the navicular bursa (NB), distal interphalangeal joint (DIPJ) and digital flexor tendon sheath (DFTS) was performed using 3, 5 and 10 mL diluted radiodense contrast medium, respectively. After each synovial injection, 25 gage needles were placed over the palmar digital nerves at the proximal aspect of the ungular cartilages (distal injections) and 1 cm further proximally (proximal injections), and CT examination was performed. Subsequently, needles were removed, and the synovial structures further distended with the same volume as for the first injection. Perineural needle placement and image acquisition were repeated. The distance between the needle tip and adjacent synovial structures was measured (mm) in reconstructed images. Results were analyzed in separate general linear mixed models, to determine the effect of needle position and synovial distension on the distance from the tip of the needle to the NB, DFTS and DIPJ. Results Synovial penetration was confirmed following 12/420 (3%) needle placements (NB n = 5, 1 after proximal and 4 after distal injections; DIPJ n = 2, DFTS n = 2, NB or DIPJ n = 3, all after distal injections). The mean distance from the needle tip to the NB and DIPJ was significantly smaller after the second distension (NB: p = 0.025; DIPJ: p < 0.001) and with the distal needle placements (NB: p < 0.001; DIPJ: p < 0.001). For the DFTS, the distance from the needle tip was significantly smaller with the proximal needle placements (p = 0.001). Main limitations Ex-vivo study. Conclusion There is a small risk of synovial penetration when performing palmar digital nerve blocks, especially when distension of adjacent synovial structures is present.